2021
DOI: 10.1088/1755-1315/788/1/012085
|View full text |Cite
|
Sign up to set email alerts
|

Study on contour feathers growth of White-rumped Shama during fledgling phase

Abstract: White-rumped Shama (Copsychus malabaricus) has become a favorite pet among Indonesian bird keepers lately. A champion bird with beautiful chirps and colours would be valued high. There are very limited scientific information on its species, and this study results will enrich the biological data. The purpose of this study was to trace and record white-rumped shama contour feathers growth including feather types and changes of size during fledgling phase. There were 8 mixed sex chicks (a crossbreed of Medan x No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 2 publications
0
9
0
6
Order By: Relevance
“…The rapid development that occurs in pubertal birds will then decrease gradually at aged 9 mo. 32 In another study, tympaniform membranes lateral were reported to be larger in male pigeons than in female pigeons. 33 This is supported by studies of the duration and number of chirping periods being greater in females than males.…”
Section: Discussionmentioning
confidence: 92%
“…The rapid development that occurs in pubertal birds will then decrease gradually at aged 9 mo. 32 In another study, tympaniform membranes lateral were reported to be larger in male pigeons than in female pigeons. 33 This is supported by studies of the duration and number of chirping periods being greater in females than males.…”
Section: Discussionmentioning
confidence: 92%
“…The rapid development that occurs in pubertal birds will then decrease gradually at aged 9 mo. 30 In another study, tympaniform membranes lateral were reported to be larger in male pigeons than in female pigeons. 31 This is supported by studies of the duration and number of chirping periods being greater in females than males.…”
Section: Discussionmentioning
confidence: 92%
“…Berdasarkan aspek budaya, kebiasaan beternak burung sebagai ternak kesayangan telah lama dilakukan oleh masyarakat Indonesia misalnya di pulau Sumatera dan pulau Jawa. Termasuk di dalamnya adalah beternak burung murai batu (Putranto et al, 2021). Hingga saat ini, aktifitas beternak burung tersebut terus berkembang semakin pesat ditinjau dari banyaknya anggota komunitas kicau mania dan peserta lomba kicau burung yang diselenggarakan di berbagai tempat di pelosok nusantara.…”
Section: Pendahuluanunclassified
“…Masalah utama yang dihadapi adalah sebelum usaha penangkaran burung murai batu dilakukan, para pecinta burung murai batu masih melakukan penangkapan bibit burung dari alam liar tanpa diikuti dengan upaya kontrol dan konservasi yang memadai. Hasil penelitian Putranto et al (2021) dan Yumiati et al (2022) mengindikasikan bahwa apabila penangkapan burung murai batu sebagai plasma nutfah ternak Indonesia dari habitat alami terus dilakukan tanpa kontrol maka dikhawatirkan akan menyebabkan penurunan populasinya di alam.…”
Section: Pendahuluanunclassified